Serum miRNA-122 is an independent biomarker of survival in patients with primary sclerosing cholangitis - Friedrich, Kilian; Wannhoff, Andreas; Rupp, Christian; Mehrabi, Arianeb; Weiss, Karl Heinz; Gotthardt, Daniel (Journal of gastrointestinal and liver diseases, 2018)
BACKGROUND AND AIMS: The disease course of primary sclerosing cholangitis (PSC) is variable and difficult to predict. MicroRNA-122 (miR-122) is associated with various liver diseases. We investigated the value of miR-122 as a biomarker for the disease course of PSC. - METHODS: We determined serum miR-122 levels in a long-term, prospective cohort of 114 PSC patients and a second validation cohort. - RESULTS: Based on miR-122 levels, PSC patients were assigned to low or high level miR-122 groups. Kaplan-Meier analysis showed significantly impaired actuarial transplant-free survival for PSC patients in the low miR-122 group (mean: 46.1 +/- 4.1 months; 95% confidence intervals [CI]: 38.1-54.2) compared to the high miR-122 group (mean: 95.2 +/- 7.9 months; 95% CI: 79.5-110.8; p = 0.034). Using a multivariate Cox's proportional hazards model approach, Mayo-Risk score (odds ratio [OR]: 1.47; 95% CI: 1.13‒1.92; p = 0.004), the presence of dominant strictures (OR: 2.62; 95% CI: 1.00‒5.55; p = 0.004), and serum miR-122 levels (OR: 1.19; 95% CI: 1.00‒1.43; p = 0.045) were independent risk factors associated with reduced actuarial transplant-free survival. We were able to confirm this finding in a second, independent cohort of PSC patients (low miR-122 group: mean survival: 13.1 +/- 5.2 months; 95% CI: 2.8-23.4; high miR-122 group: mean: 28.62 +/- 4.2 months; 95% CI: 20.3-37.0; p = 0.018). - CONCLUSIONS: We identified miR-122 as a novel, independent prognostic biomarker associated with improved survival in PSC patients. It is unknown whether exogenous miR-122 might influence the disease course of PSC patients.  .
Gesehen am 10.12.2019